2021
DOI: 10.3390/foods10081770
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Corn Varieties as Functional Ingredients for Gluten-Free Products

Abstract: Oxidative stress, one among the several factors responsible for the gluten toxicity in celiac disease, together with inflammation and duodenal mucosal injury, are only partially reduced by the gluten-free diet. Thanks to their phenolic profile, the pigmented varieties of corn could be an interesting source of dietary antioxidants for the formulation of new gluten-free ingredients. The aim of this research was: (1) to characterize the phenolic profile and the associated antioxidant properties of corn samples wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Therefore, after chemical characterization, the safety of pigmented varieties for patients with gluten intolerance was confirmed by different in vitro models (a cell agglutination test and measurement of transepithelial electrical resistance). Although in vivo studies are necessary, the data collected in the aforementioned study underline that pigmented corn could play a role in reducing oxidative stress at the intestinal level [ 59 ]. Cellular assays applied in another study confirmed the absence of alterations by pigmented strains in the permeability of the cell monolayer, a key step in the mucosal inflammatory cascade in various intestinal disorders [ 60 ].…”
Section: Phenolic Compounds and Anthocyanins In Pigmented Cornsmentioning
confidence: 99%
“…Therefore, after chemical characterization, the safety of pigmented varieties for patients with gluten intolerance was confirmed by different in vitro models (a cell agglutination test and measurement of transepithelial electrical resistance). Although in vivo studies are necessary, the data collected in the aforementioned study underline that pigmented corn could play a role in reducing oxidative stress at the intestinal level [ 59 ]. Cellular assays applied in another study confirmed the absence of alterations by pigmented strains in the permeability of the cell monolayer, a key step in the mucosal inflammatory cascade in various intestinal disorders [ 60 ].…”
Section: Phenolic Compounds and Anthocyanins In Pigmented Cornsmentioning
confidence: 99%
“…Maize is naturally rich in antioxidants and pigmented varieties of corn could be used as healthy ingredients for the formulation of novel gluten-free products [91]. The antioxidant activity of maize flour is dependent on phenolics, mainly ferulic acid, carotenoids, phlobaphenes, and anthocyanins, which confer different colours to five types of corn (white, yellow, blue, purple, and red).…”
Section: Maizementioning
confidence: 99%
“…An alternative source of anthocyanins suitable for the development of dietary supplements is the purple corn cob with a concentration range of 3.1 to 12.6 mg of cyanidin-3-glucoside equivalents/g [79,80]. Finally, red pigmentation depends on the MYB P1 gene, which activates phlobaphene accumulation (27.53 mg/g) in pericarp of maize seeds [91]. Yellow corn varieties contain lutein, zeaxanthin, β-cryptoxanthin, and β-carotenes mainly in the germ, followed by aleurone and endosperm [68,93,94].…”
Section: Maizementioning
confidence: 99%
“…Corn and rice are among the most frequently consumed cereals in GFD; their pigmented varieties could be used as innovative ingredients to improve the quality of the celiac diet [ 10 ].…”
Section: Introductionmentioning
confidence: 99%